2019
DOI: 10.1002/bio.3656
|View full text |Cite
|
Sign up to set email alerts
|

Selective sensing Ca2+ with a spiropyran‐based fluorometric probe

Abstract: Spiropyran (SP) and its derivatives operate between their ring opening and closing forms as a versatile molecular platform for the fluorescence detection of cations and anions, using a colour change for signalling. A functionalized SP fluorescence probe, L, was prepared and characterized. Probe L can detect Ca 2+ with a fluorescence 'turn-on' response in ethanol solution. It selectively binds Ca 2+ to form a 1:1 ligand/metal complex, which produced a new emission band centred at 604 nm. The sensing result was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 40 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…As an important additional result, some of the metal ions tested presented a fluorescence under UV light irradiation (Figure 7), including Ca 2+ and Mg 2+ . Other researchers have also reported this phenomenon for these ions [35,38]. Zn 2+ appears orange in color, and it was the only one in its set that presented fluorescence.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…As an important additional result, some of the metal ions tested presented a fluorescence under UV light irradiation (Figure 7), including Ca 2+ and Mg 2+ . Other researchers have also reported this phenomenon for these ions [35,38]. Zn 2+ appears orange in color, and it was the only one in its set that presented fluorescence.…”
Section: Resultsmentioning
confidence: 60%
“…In addition, to these results, the PEGSP2 solution was irradiated by cycling UV and visible lights, Figure 5b, demonstrating that PEGSP2 could have a better isomerization efficacy than SPCOOH, after 10 cycles there is a 16.2% decrease in absorbance. Recent literature [35,36,37] also reports SP dyes as sensors, mainly in solution. Based on our data, twenty-five metals ions in aqueous solution were tested on the PEGSP2 nanofibers surface.…”
Section: Resultsmentioning
confidence: 99%
“…Through comparison, it is found that the LODs of Zn 2+ , Cu 2+ , and Sn 2+ in our work can reach 0.054, 0.038, and 0.049 μm, respectively, which is the lowest detection concentration reported so far. At present, a lot of references have reported that the introduction of special groups into spiropyran can realize the specific recognition of metal ions. Combining the innovations of this work with reported references, a metal ion sensor with high fluorescence EF, low LOD, and excellent specific recognition will be fabricated, providing a new idea for the follow-up research in this field.…”
Section: Resultsmentioning
confidence: 78%
“…Wang’s group 52 constructed a spiropyran probe, 15 ( Figure 14 ), to recognize the Ca 2+ ion through a “turn-on” response. An electron-withdrawing cyano group was introduced in the probe to facilitate isomerization by weakening the C–O bond of the closed SP form.…”
Section: Cation Chemosensorsmentioning
confidence: 99%